Perovskite Solar Cell Stability in Humid Air: Partially Reversible Phase Transitions in the PbI2‐CH3NH3I‐H2O System. Issue 19 (8th July 2016) - Song, Zhaoning; Abate, Antonio; Watthage, Suneth C.; Liyanage, Geethika K.; Phillips, Adam B.; Steiner, Ullrich; Graetzel, Michael; Heben, Michael J.
Abstract : After rapid progress over the past five years, organic–inorganic perovskite solar cells (PSCs) currently exhibit photoconversion efficiencies comparable to the best commercially available photovoltaic technologies. However, instabilities in the materials and devices, primarily due to reactions with water, have kept PSCs from entering the marketplace. Here, laser beam induced current imaging is used to investigate the spatial and temporal evolution of the quantum efficiency of perovskite solar cells under controlled humidity conditions. Several interesting mechanistic aspects are revealed as the degradation proceeds along a four‐stage process. Three of the four stages can be reversed, while the fourth stage leads to irreversible decomposition of the photoactive perovskite material. A series of reactions in the PbI2 ‐CH3 NH3 I‐H2 O system explains the interplay between the interactions with water and the overall stability. Understanding of the degradation mechanisms of PSCs on a microscopic level gives insight into improving the long‐term stability. Abstract : State‐of‐the‐art perovskite solar cells are examined under accelerated aging conditions using fast laser beam induced current imaging. The results demonstrate that the degradation of perovskite solar cells in the presence of water is a four‐stage process involving phase transformations of the perovskite material. The work allows a detailed understanding of the evolution and mechanisms of moisture‐induced perovskite degradation on a microscopic scale.